2005
DOI: 10.1093/jxb/eri136
|View full text |Cite
|
Sign up to set email alerts
|

Localization of aluminium in the maize root apex: can morin detect cell wall-bound aluminium?

Abstract: Morin is a fluorochrome which forms a fluorescent complex with aluminium (Al) and is thus used to localize Al in plant tissues. However, reports about the cellular distribution of Al-apoplastic versus symplastic-based on morin staining are often conflicting. The objective of this work was to investigate whether Al localization with morin staining can show the proper cellular distribution of Al. Fresh root cross-sections were made from root apices of maize (cv. Lixis) treated with 25 muM Al for 6 h and stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…Morin can detect Al inside the cells but cannot detect cell wallbound Al. 9 This result is consistent with Al concentration in the root cell sap of overexpressed lines (Fig. 3B).…”
supporting
confidence: 87%
“…Morin can detect Al inside the cells but cannot detect cell wallbound Al. 9 This result is consistent with Al concentration in the root cell sap of overexpressed lines (Fig. 3B).…”
supporting
confidence: 87%
“…7 and 8). As morin staining was reported to be not a good index of Al bound to cell wall pectin, but it could detect Al bound to phosphate (Eticha et al, 2005), therefore our results clearly indicated that immobilization of P with Al in cell wall was involved in high Al resistance in buckwheat.…”
Section: Kochian (2002) Also Found That Hmentioning
confidence: 53%
“…Morin can detect aluminum in the cytosol but not cell wall-bound aluminum or vacuole-compartmentalized aluminum (Eticha et al, 2005b;Huang et al, 2012). The lack of morin staining in vacuole may be attributed to two reasons according to Huang et al (2012): (1) morin is not permeable to the tonoplast, and (2) vacuolar aluminum is chelated by organic reagents, such as malic and citric acids, and morin cannot detect complexed aluminum forms, similar to cell wall-bound aluminum (Eticha et al, 2005b). Therefore, strong aluminumdependent green fluorescence represents aluminum present in the cytosol and nucleus.…”
Section: Resultsmentioning
confidence: 98%